What are the zeros of the function below? Check all that apply.
F(x) = (x+3)(x - 1)
(x-2)(x + 2)

A.-2

B.-3

C.-5

D. 2

E. 3

F. 1

Thank you in advance!

Respuesta :

Answer:

A, B, D, F

Step-by-step explanation:

Given

f(x) = (x + 3)(x - 1)(x - 2)(x + 2)

To find the zeros let f(x) = 0, that is

(x + 3)(x - 1)(x - 2)(x + 2) = 0

Equate each factor to zero and solve for x

x + 3 = 0 ⇒ x = - 3 → B

x - 1 = 0 ⇒ x = 1 → F

x - 2 = 0 ⇒ x = 2 → D

x + 2 = 0 ⇒ x = - 2 → A

Answer:

A, B, D, F

Step-by-step explanation:

ACCESS MORE